Lateral Canthal Tendon Disinsertion: Clinical Characteristics and Anatomical Correlates. Issue 5 (September 2016) - Shriver, Erin M.; Erickson, Benjamin P.; Kossler, Andrea L.; Tse, David T.
Abstract : Purpose: To highlight features of lateral canthal tendon disinsertion (LCTD), provide an algorithm for systematic assessment, and describe the anatomic genesis of signs and symptoms. Methods: Retrospective case series of consecutive patients with lateral canthal tendon disinsertion, who underwent lateral canthal tendon fixation by a single surgeon (DTT) between 2004 and 2011. Results: One hundred and seventeen eyes in 90 patients underwent lateral canthal tendon fixation. Average age was 69.3 ± 17.9 years. Twenty-three percentage of eyes had undergone lower eyelid blepharoplasty and 52% had undergone lateral canthal tightening; 35% had no previous periocular surgery. Patients with purely involutional lateral canthal tendon disinsertion were significantly older (76.1 ± 7.8 years of age; p < 0.03). Six key features associated with lateral canthal tendon disinsertion were identified. On static evaluation: 1) a blunted or vertically displaced lateral canthal angle; 2) a narrow horizontal fissure with reduced temporal scleral triangle; and 3) pseudo eyelid retraction. On dynamic evaluation with attempted closure: 4) medial and inferior movement of the lateral commissure; 5) incomplete apposition of the eyelid margins in the absence of anterior lamellar shortage; and 6) temporal eyelid imbrication. Improved blink dynamics with manual lateral canthal tendon complex repositioning ("the thumb test") predicted a favorable outcome with surgical tightening in 95.7% of cases. Conclusions: Lateral canthal tendon disinsertion results in altered eyelid fissure symmetry, blink dynamics, and lacrimal pump function. The authors recommend the mnemonic—A.B.C.: for A perture configuration, B link dynamics, and eyelid C losure—to structure the examination of all symptomatic patients. Manual restoration of the disinserted lateral canthal tendon with the "thumb test" predicts favorable outcomes with surgical fixation. Abstract : Lateral canthal tendon disinsertion is an anatomic defect that alters eyelid fissure symmetry, blink dynamics, closure, and lacrimal pump function. The authors describe clinical characteristics, and present a mnemonic and "thumb test" for assessment.